A model for the formation of airborne particulate matter based on the gas-phase adsorption on amorphous carbon blacks. - Risby, T H (1988)
This paper reports the physicochemical properties that describe the adsorption of a series of solutes onto the surfaces of amorphous carbon blacks. Adsorption was studied at concentrations that correspond to low surface coverages and in the presence of volatile solvent diluents. The adsorbates and adsorbents were selected for their relevance as models for environmental agent-particle complexes originating from incomplete combustion. The data clearly show that the major factors that determine the strength of adsorption are the surface properties of the adsorbent and the intermolecular forces between the surface and the adsorbing molecule. The heat of adsorption data have been used to predict the lifetime of the absorbate-adsorbent complexes.